Analisis Kesesuaian Praktek Pembiayaan Musyarakah KSPPS BMT Al-FATH Menurut Fatwa No. 08/DSN-MUI/IV/2000 - Setiawan, Ijlal; Justa, Abrizen (Department of Islamic Economics Law, 2024)
This research aims to determine the level of conformity in the Implementation of Musyarakah Financing at BMT AL-FATH with the Decree of the National Sharia Board of the Indonesian Ulema Council (DSN-MUI) No. 08/DSN-MUI/IV/2000 and to identify the juridical implications for BMT if it is proven to violate the Decree of the National Sharia Board of the Indonesian Ulema Council (DSN-MUI) No. 08/DSN-MUI/IV/2000 in its implementation. This study employs a qualitative descriptive method applied through formative evaluation research. It utilizes primary data sources through interviews, observations, documentation, and their combination, as well as secondary data obtained from books, journal articles, government publications, company documentation records, websites, laws, and fatwas. Data analysis involves data reduction, data presentation, and drawing conclusions. The research results indicate that BMT Al-Fath has successfully implemented the musyarakah contract in accordance with the Fatwa of the National Sharia Board of the Indonesian Ulema Council No. 08/DSN-MUI/IV/2000, comprising 22 provisions outlined in the fatwa, and has not been negatively affected by the legal provisions contained in Law No. 21 of 2008, Article 58, concerning Islamic banking.